Hepatoprotective Effect of Parijoto Fruit Extract (Medinilla speciosa Blume) on Male Mice Fed with High-Fat Diet - Nabila, Inasa; Thadeus, Maria Selvester; Herardi, Ryan (Jurnal Gizi dan Pangan, 2023)
This study aims to determine the effectiveness of parijoto fruit extract (Medinilla speciosa Blume) in improving the condition of fatty liver in male balb/c mice (Mus musculus L.) fed with a high-fat diet. Thirty male balb/c mice weighing 20 to 30 g were randomly divided into six groups, i.e: 1) Standard feed and Carboxymethyl Cellulose Sodium or CMC-Na 0.5% (K1); 2) High-fat diet and CMC-Na 0.5% (K2); 3) High-fat diet and simvastatin 0.026 mg/day (K3); 4) High-fat diet and parijoto fruit extract 5.6 mg/20 g BW (P1); 5) High-fat diet and parijoto fruit extract 8.4 mg/20 g BW (P2); 6) High-fat diet and parijoto fruit extract 11.2 mg/20 g BW (P3). Standard feed, high-fat diet, simvastatin, and parijoto fruit extract were administered for 56 days. On the 57th day, the total of 30 mice were terminated and the livers were then removed for H&E staining histopathological slides. Data on the degree of fatty liver on histopathological slides were collected and analyzed using the Kruskal-Wallis test and followed by the Mann-Whitney test. The histopathological analysis showed Medinilla speciosa Blume extract at a dose of 5.6 mg/20 g BW in group P1 prevent the steatosis degree compared to high-fat feed mice in group K2 (p>0.05). Parijoto fruit extract could act as the potential treatment for fatty liver.